2002
DOI: 10.1137/s1052623401395061
|View full text |Cite
|
Sign up to set email alerts
|

Shape Optimization in Contact Problems with Coulomb Friction

Abstract: The present paper deals with shape optimization in discretized two-dimensional (2D) contact problems with Coulomb friction, where the coefficient of friction is assumed to depend on the unknown solution. Discretization of the continuous state problem leads to a system of finite-dimensional implicit variational inequalities, parametrized by the so-called design variable, that determines the shape of the underlying domain. It is shown that if the coefficient of friction is Lipschitz and sufficiently small in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 27 publications
0
40
0
1
Order By: Relevance
“…A similar situation arises in discretized contact problems with Coulomb friction, cf. [1] and [2]. The GE considered here differs, however, considerably from the corresponding GE in the case of 2D contact problems with Coulomb friction.…”
Section: Introductionmentioning
confidence: 89%
“…A similar situation arises in discretized contact problems with Coulomb friction, cf. [1] and [2]. The GE considered here differs, however, considerably from the corresponding GE in the case of 2D contact problems with Coulomb friction.…”
Section: Introductionmentioning
confidence: 89%
“…Subgradients were computed for the problems written as variational inequalities in [33] and [51]. It yields a better accuracy on the normal force and gives good results for optimisation with Coulomb friction [7]. Note…”
Section: Examples In 3dmentioning
confidence: 99%
“…For this last model of friction, the uniqueness of the contact solution is not ensured for the continuous model and examples of non-uniqueness can be built. Consequently, in [7] and [8], the authors analyse the derivation of the discretised problem, which admits a unique solution for small friction coefficients, by using subgradient calculus. Eventually, a thorough review of other results in shape optimisation for contact problems can be found in [31].…”
Section: Introductionmentioning
confidence: 99%
“…We have solved Problem 10 defined by (23) for different values of parameter q. The calculated torque is presented in Fig.…”
Section: The Effect Of Value Of the Control Parameter Q Problems 10 mentioning
confidence: 99%
“…Optimization problems with frictional contact were investigated in [23][24][25][26][27][28][29][30]. Special methods (level set method, evolutionary approach) were also used for topology optimization [31,32].…”
Section: Introductionmentioning
confidence: 99%